Health and safety improvement in construction projects: a lean construction approach - Abu Aisheh, Y.I. (Taylor and Francis Ltd., 2021)
Objectives. Lean construction techniques have been considered an effective approach and strategy to reduce accidents in construction projects. This article aims to investigate the application of the lean construction principle and its impact on occupational health and safety. Methods. To achieve the aim, an analytical descriptive method was used. The data were collected through a questionnaire, with 70 respondents who were chosen using a random stratified sample method. The questionnaire evaluated the perception of contractors and consultants about the important lean construction factors and their impact on construction project safety. Results. There is an agreement that the application of lean construction techniques can be impeded by challenges like lack of lean construction knowledge, complexity, misconception about lean construction and difficulties in changing employees. Conclusions. The study identified strategies that could be used to address these challenges that will improve the safety of construction projects. These include enlightenment on benefits of the lean practice, publication of improvements realized from lean practice, training, workersâ involvement and empowerment, persistence, robust planning and gradual implementation. Â© 2021 Central Institute for Labour ProtectionâNational Research Institute (CIOP-PIB).